Modern Perspectives in Business Applications - Abdul Rehman Khan, Syed; Ilgaz Sümer, Selay (IntechOpen, 2020)
This book is unique! Until now, purchasing and supply management books have had a primarily domestic outlook. However in this book, important issues related to sales management and supply management are handled with a modern perspective. This book has global vision tied into management principles based on an understanding of the sales management and basic job of purchasing and supply management, as all authors have held high-level positions directing the effort. Distinguished researchers from prestigious universities have written chapters and case studies from real-world events that challenge the brightest minds.